"ALTJMIR IN BOUATH ITS POLITICAL AND SOCIAL EFFECTS IN THE RASHIDUN AND UMAYYAD ERAS"(23/662- 132/750) (Journal of Human Sciences, 2025)
The prolonged presence of soldiers on the battlefronts or to guard the borders of the Islamic Arab state was a necessity imposed by the expansionist military policy at the dawn of Islam. However, it soon became a means of collective punishment for regions with political opposition; to weaken their strength, and engage them with the lurking enemy, instead of being occupied with the policies of the caliphs and governors, a practice that became prevalent during the Umayyad era. As a result of this approach, there were political and social repercussions on the people, such as hatred towards Umayyad rule and its tyranny in forcing them to go out to wars and stay for long periods on the enemy's borders in harsh conditions, far from their families and fellow citizens.